2017
DOI: 10.1007/s11200-016-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Data requirements for a 5-mm quasi-geoid in the Netherlands

Abstract: We assess the surface gravity data requirements for a 5-mm quasi-geoid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For comparison purposes, the accuracy of gravimetry using modern relative gravimeters, such as Scintrex CG-6, is from 0,001 to 0,003• 10 -5 m s -2 . Required accuracy for geological exploration is around 0,01• 10 -5 m s -2 , for explorations of the oil, gas and minerals around 5• 10 -5 m s -2 (Seigel, 1995), for geoid determination from 1 to 5• 10 -5 m s -2 (Farahani et al, 2017). Solutions using DEMs with resolutions 5″, 10″ and 15″ for most of the areas have differences smaller than 1• 10 -5 m s -2 , which for only rare applications can be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison purposes, the accuracy of gravimetry using modern relative gravimeters, such as Scintrex CG-6, is from 0,001 to 0,003• 10 -5 m s -2 . Required accuracy for geological exploration is around 0,01• 10 -5 m s -2 , for explorations of the oil, gas and minerals around 5• 10 -5 m s -2 (Seigel, 1995), for geoid determination from 1 to 5• 10 -5 m s -2 (Farahani et al, 2017). Solutions using DEMs with resolutions 5″, 10″ and 15″ for most of the areas have differences smaller than 1• 10 -5 m s -2 , which for only rare applications can be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…This is a consequence of insufficient accuracy and density of the mean terrestrial gravity anomalies that were used in the computations. The role of the terrestrial gravity data accuracy for the quality of the calculated geoid model is explained by [83,84]. In accordance with a 1-2 mGal accuracy of the terrestrial gravity data, having 1-2 km spatial resolution with homogenous distribution is required if 1-2 cm accuracy of the geoid undulations is aimed.…”
Section: Testing the Ggms Contribution In Detailed Geoid Modelingmentioning
confidence: 99%
“…It was revealed that a minimum data spacing of 5 km without data gaps with a data noise between 0.1-0.5 mGal is suitable to achieve 5 mm geoid accuracy using the KTH method. Farahani et al (2017) assessed the surface gravity data requirements for a 5-mm quasi-geoid model considering the omission and commission errors. The study identified the relationship between omission error and data resolution as well as commission error and data accuracy.…”
Section: Introductionmentioning
confidence: 99%